1999
DOI: 10.1080/001731300750044582
|View full text |Cite
|
Sign up to set email alerts
|

Pollen walls of Araceae, with special reference to their fossilization potential

Abstract: M. 1999. Pollen walls of Araceae, with special reference to their fossilization potential. ± Grana 38: 203±209. ISSN 0017-3134.Araceae, a basal monocot family, has a very poor fossil record, especially with regard to pollen grains. An ultrastructural study of Araceae pollen walls was undertaken to answer the questions: which pollen is resistant to decay and will appear in the fossil record? and which pollen has a smaller fossilization potential and why? The wall strata of Araceae pollen differ in morphology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…In Aroideae pollen grains, generally a quite irregular infolding occur because of the lack of any stabilizing element in these omniaperturate pollen grains. However, endexines are (rather surprisingly) chemically more stable and, hence, may be more resistant to decay than the ektexines (Rowley et al, 1990;Hesse et al, 1999); this would support the hypothesis of the endexine being the only stable pollen wall element in Aroideae.…”
Section: Case Of the Thick Spongy Endexinementioning
confidence: 56%
See 1 more Smart Citation
“…In Aroideae pollen grains, generally a quite irregular infolding occur because of the lack of any stabilizing element in these omniaperturate pollen grains. However, endexines are (rather surprisingly) chemically more stable and, hence, may be more resistant to decay than the ektexines (Rowley et al, 1990;Hesse et al, 1999); this would support the hypothesis of the endexine being the only stable pollen wall element in Aroideae.…”
Section: Case Of the Thick Spongy Endexinementioning
confidence: 56%
“…The aperigoniate Aroideae are characterized by two synapomorphies, the invariably omniaperturate pollen grains sharing an outermost exine stratum which is not resistant to acetolysis and further on by a thick, spongy endexine which is finished earlier than the outermost exine layer (e.g. Arum: Pacini and Juniper, 1983, and Sauromatum: Weber et al, 1998; Hesse et al, 1999). Additionally, the absence of callose and primexine was reported for Arum (Anger, 2001;Anger and Weber, submitted for publication).…”
Section: Introductionmentioning
confidence: 87%
“…The exine is also only weakly developed and susceptible to acetolysis, which also removes the thick intine (32). Low resistance of exine to acetolysis is thought to correlate with low fossilization potential (29).…”
Section: C-f and H)mentioning
confidence: 99%
“…Palynology has played an important role in angiosperm taxonomy (Erdtman 1966;Walker and Doyle 1975), including those of the Araceae (e.g., Weber et al 1998Weber et al , 1999Hesse et al 1999;Hesse et al 2001;Zetter et al 2001;Van der Ham et al 2005). To our knowledge, however, palynological study of the genus Symplocarpus has not been reported due in part to its relatively small number of species and its weak exine, which is disintegrated during acetolysis.…”
Section: Introductionmentioning
confidence: 87%